Fermented Alfalfa Meal Instead of “Grain-Type” Feedstuffs in the Diet Improves Intestinal Health Related Indexes in Weaned Pigs - Luo, Yuheng; Liu, Yang; Shen, Yuqing; He, Jun; Li, Hua; Lan, Cong; Li, Jiayan; Chen, Hong; Chen, Daiwen; Ren, Zhihua; Yu, Bing; Huang, Zhiqing; et al. (Frontiers in Microbiology, 2021)
Corn and soybean meal are the two main components in formula feed of farm animals, leading to a serious food competition between humans and livestock. An alternative may be to encourage the utilization of unconventional feedstuff in animal diet. In the current study, we evaluated the utilization of fermented alfalfa meal (FAM) in weaned pigs. Twenty weaned piglets (separately caged) were randomly divided into two groups. Pigs in the control group (CON) were fed corn-soybean meal diet, and part of corn and soya protein concentrate in the diet of another group was replaced by 8% FAM. After 40 days of feeding, the average feed intake of FAM pigs was higher (P > 0.05), and the villus height (VH) of jejunum and duodenum, crypt depth (CD) and VH/CD in FAM pigs was improved compared to CON group (P < 0.05). The increase (P < 0.05) of goblet cells in the jejunum of FAM pigs was positively correlated with the expression of MUC-2 gene (R = 0.9150), and the expression of genes related to immunity (IRAK4, NF-κB and IL-10) and intestinal barrier (Occludin and MUC-2) in the jejunum, as well as the expression of ZO-1 and MUC-2 in the colon of these pigs also showed increased (P < 0.05) compared to CON pigs, which was accompanied by the decrease (P < 0.05) of LPS concentration in the serum. The elevated proportion of CD3+ and CD8+ T-lymphocyte subsets in spleen (P < 0.05) confirmed the improvement of systemic immune function in FAM pigs. In addition, the β-diversity of microbial community in the colon of FAM pigs also showed increased compared to CON pigs (P < 0.05), and the enrichment of probiotics such as Lactobacillus that positively correlated with acetate concentration was promoted (P < 0.05). In summary, using 8% FAM partially (8%) instead of expanded corn and soya protein concentrate may benefit the intestinal barrier and immune function of weaned pigs without affecting their growth. Our findings also provide evidences of the feasibility of FAM as a dietary component in pigs to reduce the consumption of grain.